Hubungan Pengeodalian Diri Dengan Kebiasaan Merokok Pada Remaja Di Sman I GedegKabupaten Mojokerto - Nur Hidayati, Rina; Zainuri & Elisa Kharisma Agustina, Imam (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractThe ability to self-control is one of adolescent needs that must be met adolescent needs self-control because generally at the period of (storm and stress). If adolescents has poor self-control can cause misbehaviour such as smocking. Smoking is one of the habit that found in daily life. This researche purposed to know about relationship or self-control with adolescent smoking habit. This disain of researche was analytic correlation with cross sectional approach. The populationin this researche were 40 male students who smoked at SMAN I Gedeg Mojokerto. The technique of samples using purposive sampling with 40 male students who smoked. Using instrument such as questionnaire both self-control and smoking habit. Data printed on SPSS program using Chi Square Test. This researche showen most of the students has poor self-control as many as 22 people (55%) and nd light smokers consider smoking as many as 27 people (67.5%). On correlation Chi Square test was obtined calculation results with significant values (p) = 0.00 I, while a= 0.05. Because of significant value (p = 0.001 <a = 0.05) it means there was relations about self-control with smoking in adolescents. School institution of SMAN 1 Gedeg Kabupaten Mojokerto should be willing to provide guidance and specialized counseling to students who have poor control so that studentscan he disciplined and he aware of the dangers of smoking.Keywords: Adolescent, Self-Control , Smoking Habit